2007
DOI: 10.1038/sj.ejcn.1602853
|View full text |Cite
|
Sign up to set email alerts
|

Under- and overnutrition dynamics in Chinese children and adults (1991–2004)

Abstract: Objective: To examine trends in under-and overweight prevalence from 1991 to 2004 among adults and children in China by income and residence differentials. Methods/Subjects: Prevalence, average annual changes and annual relative changes in under-and overweight were determined. In 1991, 2848 children and 6806 adults were surveyed. The 2004 survey included 1566 children and 6172 adults. Results: Higher average annual reductions in underweight prevalence were found among children, particularly rural children, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
57
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 31 publications
7
57
1
Order By: Relevance
“…For example, Dearth-Wesley et al found that between 1991 and 2004, the prevalence of overweight increased faster among low-income than highincome Chinese adults. 7 These different trends for adults and children could stem from a shift in the control of children's and adolescents' food choices, from parents to their children. Children have a strong preference for sweet and fatty foods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Dearth-Wesley et al found that between 1991 and 2004, the prevalence of overweight increased faster among low-income than highincome Chinese adults. 7 These different trends for adults and children could stem from a shift in the control of children's and adolescents' food choices, from parents to their children. Children have a strong preference for sweet and fatty foods.…”
Section: Discussionmentioning
confidence: 99%
“…7 This study found that overweight prevalence increased fastest among high-income children between 1991 and 2004. To date, however, no study has thoroughly explored the contextual factors contributing to the changing relationship between SES and overweight and obesity in children and adolescents, in China or in any other developing country.…”
mentioning
confidence: 93%
“…For girls, family and district income was not associated with overweight or obesity, though rural hukou status was associated with a lower risk of overweight/obesity. For girls in these families, lower body weight may reflect patterns found in rural parts of the country, where the nutritional transition may not be as advanced as it is in Shanghai [36]. The importance of hukou status may also be a proxy for a variety of other unobserved variables, for example, access to social and economic resources, which may matter for child weight.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless we have shown elsewhere that the BMI distribution for Chinese of all ages has shifted markedly higher and few children or adults have a low BMI. There are some instances of underweight among adults over seventy-five years old (Dearth-Wesley et al, 2008; Gordon-Larsen et al, 2014; Ji and Cheng, 2008; Popkin, 2006). …”
Section: Discussionmentioning
confidence: 99%